Geometrical forms, model and space concept in interior architecture education - Eceoğlu, Arzu (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2015)
As an example for "Interior Architecture" educations given in various faculties of universities, this work is on creating space designs via models, which are made to establish the understanding of students on scale, rate and ratio. The syllabus of Interior Architecture departments aims to develop the students' understanding on space and have them get better results in terms of perception. What really matters is for student to understand the space concept and get the knowledge required for reaching the right conclusions on space organization. In the later stages, created by the usage of different materials with the aim of developing space design integrity, student projects are supported to make a difference in collaboration with arts and science. The aim of this work is to analyze and show the development of design concept through the models prepared within the extent of space organization courses, the roles of geometrical forms during the design phase and the setup of the models created, by using Le Courbisie's first house model named cell.
Keywords: Interior architecture; Space organization; Le courbisie; Design phase; Model